Introduction - Sári B., László (FOCUS: Papers in English Literary and Cultural Studies, 2025)
The introduction frames the issue’s focus on the dynamic relationship between literature and institutional contexts, highlighting how literary production, interpretation, and circulation are shaped by social, cultural, and academic frameworks. It outlines the contributions, which explore topics ranging from historical reading practices and political theatre to economic criticism, digital humanities, and representations of elite education. The review section is also introduced, emphasizing recent scholarship on Wharton, Irish drama, feminist tragedy, and True Crime. Overall, the issue presents a diverse set of approaches to understanding how institutions influence literary meaning and practice.